Pediatric lung function testing during a pandemic: An international perspective. (November 2020) - Beydon, N.; Gochicoa, L.; Jones, M.J.; Lands, L.C.; Lombardi, E.; Rosenfeld, M.; Sly, P.D.; Weiner, D.J.; Yilmaz, O.
Highlights: Pulmonary function testing laboratories needed to reorganize during the COVID-19 pandemic. Protection of patients, families and professionals performing pulmonary function testing is a primary concern. Certain changes in laboratory organization and procedures implemented during the pandemic may become permanent. Abstract: The COVID pandemic has passed its first peak for now in many countries while some are still on the rise, with some facing a second wave of cases. Precautions and infection control measures for both pediatric and adult pulmonary function testing (PFT) have been a topic of debate during the pandemic. Many centers had to close their PFT laboratories during the initial periods of the pandemic and are reopening as the numbers of new cases are decreasing. This review aims to summarize different practices of PFT laboratory management in different countries, including patient appointments, personal protective equipment, testing room requirements and telemedicine during and immediately following the COVID pandemic.